PENGARUH KOMUNIKASI ANONIM ANTAR-PEMAIN ROBLOX TERHADAP KARAKTER RELIGIUS SISWA KELAS III SDN BUDHI KARYA - Alyssa Martjha Irawan; Muhammad Abdan Syakuro; Rahma Aulia; Zahira Alifia; Hilman Taufiq Abdillah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the profile of anonymous communication among Roblox online game players, identify the profile of students' religious character, and examine the influence of such anonymous communication on the religious character of third-grade students at SDN Budhi Karya. In the digital era, Roblox has become a widely used virtual social interaction space for children, where features like usernames, avatars, and chat options enable communication without revealing real identities (anonymity). This quantitative research utilized an ex post facto method with a correlational design. The research sample was selected using a total sampling technique, involving all 64 third-grade students at SDN Budhi Karya. Data collection was comprehensively conducted through questionnaires, direct observation, and interviews. The research instruments were proven valid and reliable, with Cronbach’s Alpha values of 0.821 for the anonymous communication variable and 0.881 for the religious character variable. The data analysis stages included prerequisite analysis and hypothesis testing, consisting of normality, linearity, and Pearson correlation tests. The normality test results showed a significance value of 0.075 (normally distributed data), and the linearity test indicated a significance value of 0.467 (the relationship between the two variables is linear). Furthermore, the Pearson correlation test yielded a correlation coefficient value of 0.066 with a significance value of 0.605. Based on these analytical results, since the significance value is greater than 0.05, H₀ is accepted and H₁ is rejected. Consequently, it can be concluded that there is no significant influence of anonymous communication among Roblox players on the religious character of third-grade students at SDN Budhi Karya.